Peningkatan Hasil Belajar Pendidikan Agama Islam melalui Metode Sing a Song di SDN Sumberejo II, Purwosari, Pasuruan - Nur Aisyah, Farihah Mar'atul Khiyaroh Taufiq; Wiwin Fachrudin Yusuf (IAIN Ambon, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education (IRE) on the topic of Aqil Baligh by using the Sing a Song learning method. The research was conducted at SDN Sumberejo II with the subjects being 18 fourth-grade students. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was carried out in two cycles. Data collection techniques included participatory observation, interviews, documentation, and learning outcome tests. The results showed a significant improvement in student learning outcomes, where in the pre-action stage using conventional lecture methods, the percentage of completeness only reached 33.3% (6 students). In Cycle I, with the implementation of the Sing a Song method, the percentage of completeness increased to 61.1% (11 students), and in Cycle II, with the development of group song creation activities, the percentage of completeness reached 94.4% (17 students). This study concludes that the Sing a Song method, combined with group activities in creating songs, is effective in enhancing students' understanding of the Aqil Baligh material while also developing their creativity and collaboration skills.